(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The growing applications of the Internet of Things lead to a constant rise in cyberattacks across the board. Identity management is one of the most common attack vectors since it enables impersonation and bypasses existing trusted procedures. The weak identity management approach undermines any attempt to create safe systems because identity is fundamental to every security mechanism, including authentication and access control. Although digital certificates are the most popular methods for authentication and identification, their widespread distribution is still unresolved. The procedure includes identity and key provision for devices which is typically a laborious undertaking. The human-made configuration might have mistakes and are frequently the root for many security and privacy problems. This operation should be made semi-autonomous to reduce incorrect setups while performing it. With suitable multi-key exchange authentication for user identification and a blockchain hash key, both the user and data providers can be ensure with authentication, authorization, and data validity so that the data is stored and validated each time when a user accesses it. This paper aims to demonstrate the implementation to prove that without releasing information like the public key there is a possibility of enhancing the anonymity of Blockchain by using Zero Knowledge proof to IoT systems.